A Genre Analysis of Science and Technology Scopus-Indexed Journal Articles: Does Impact Factor Project Different Rhetorical Moves? - Suryawinata, Violita Zarkasih; Eri Kurniawan; Arif Husein Lubis (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Productivity in conducting research and publishing articles is the obligation of lecturers as academics. However, due to their failure to follow international writing conventions, they have difficulties in writing for international publications. Various studies have investigated the rhetorical move of research articles; however, much still needs to be investigated on the rhetorical move of the research articles written by highly reputable lecturers by comparing their publications in low-impact versus high-impact Scopus-indexed journals. This study aims to analyse the rhetorical structures of research articles in low and high-impact articles written by highly reputable lecturers in one of the universities in West Java in science and technology. Eight research articles were analysed through the framework of the move proposed by Maswana et al. in 2015. The results showed similarities and differences between the two groups. Stating a purpose, methods, and results in the abstract section was obligatory. In the method section, recounting an experimental process was always present in both groups. Interestingly, the difference was shown in stating the research implications in the conclusion part, where high-impact frequently used the move more than low-impact articles. The results show that the impact factor partly projects rhetorical moves in the research articles. This study is expected to be a useful reference for Indonesian lecturers to develop their awareness of writing an impactful research article.